KARAKTERISTIK KLINIS CEDERA KEPALA PADA PEDIATRI DI RSUP SANGLAH DENPASAR TAHUN 2020 - Gunawan, Made Favian Budi; Maliawan, Sri; Mahadewa, Tjokorda Gde Bagus; Niryana, I Wayan (Universitas Udayana, 2022)
Head injury is one of many emergency cases in pediatric with high mortality cases. The incidence of pediatric head injury in the world, is in the range of 47-280 per 100,000 inhabitants and a total of more than 3 million cases of head injury in children occur each year. This study aims to find out more about the clinical characteristics of head injuries in children, especially patients treated at Sanglah Hospital Denpasar in 2020. This study was conducted using a cross-sectional descriptive method using secondary data in the form of patient medical records. From the results of the research conducted, it was obtained as many as 86 cases, with the conclusion that the most cases were in the group of adolescent patients, in the age range of 13-18 years (62.8%), with the most mechanism of injury due to traffic accidents without the use of helmets (47.7%), then the most frequent GCS values ??were in the range 14-15 which were classified as mild head injury (55.8%), the most common complaint was headache (79.1%), the most common skull fractures were linear fractures (41 ,9%) and intracranial lesions with the most frequency were epidural hematomas (46.5%). The findings of this study are expected to be used as a basis for further research in pediatric head injury and to increase community awareness about child safety.